Support of mothers in a difficult living situation in the House of Single Mother in Łódź - Jóźwiak‑Majchrzak, Wioletta (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
This article records the observations and reflection on the practice of social work carried out in the Single Mother’s Home in Łódź, based on internal program documents.